FIGURATIVE LANGUAGE IN THE WEEKND’S MY DEAR MELANCHOLY - Damardjati , Lanang; Hardiany , Dewi Rosnita (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2023)
The relationship between language and lyrics is fascinating, since music and language's blend together. "Lyrikos" in Greek means "sung to the lyre," indicates the connection to performance art. Figurative language is a language that are not meant to be taken literally or understood in ways that normally understood. Through the use of Perrine's theory, the paper exploring what is the most used figurative language and how the artist uses figurative language in their writing. Within My Dear Melancholy EP by Canadian singer The Weeknd, there are 33 data of metaphor, conveying feelings of melancholy and heartbreak. Symbolism with 18 data, used to express deep ideas related to emotional struggles and heartache. And irony with 15 data, used to adds depth to the lyrical narrative. The Weeknd clever application of linguistic devices gives the story more depth using metaphor, symbolism, and irony to explore the complexities of heartbreak and emotional struggle.